Change in Atrial Activation Pattern during Ablation of Atrial Flutter - Akbarzadeh, Mohammad Ali; Alizadeh Diz, Abolfath; Bahrololoumi Bafruee, Negar (International Journal of Cardiovascular Practice, 2016)
Different types of supraventricular tachycardia have been reported in patients with history of surgical repair of Tetralogy of Fallot. This report presents appearance of focal atrial tachycardia during radiofrequency ablation of the cavotricuspid isthmus